7x-77=11x+35

Simple and best practice solution for 7x-77=11x+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-77=11x+35 equation:


Simplifying
7x + -77 = 11x + 35

Reorder the terms:
-77 + 7x = 11x + 35

Reorder the terms:
-77 + 7x = 35 + 11x

Solving
-77 + 7x = 35 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-77 + 7x + -11x = 35 + 11x + -11x

Combine like terms: 7x + -11x = -4x
-77 + -4x = 35 + 11x + -11x

Combine like terms: 11x + -11x = 0
-77 + -4x = 35 + 0
-77 + -4x = 35

Add '77' to each side of the equation.
-77 + 77 + -4x = 35 + 77

Combine like terms: -77 + 77 = 0
0 + -4x = 35 + 77
-4x = 35 + 77

Combine like terms: 35 + 77 = 112
-4x = 112

Divide each side by '-4'.
x = -28

Simplifying
x = -28

See similar equations:

| -5-x=4x+30 | | -5-x=4x+30 | | 10x-2-6x=2(2x-1) | | 18+4(z)+54= | | 2x-250=2858 | | 11y/45-8/9 | | 3z-3=-9 | | 5v+12=37 | | -4=7x-2x-9 | | h-5.5=3.1 | | 3/20=122/x | | (4-x)6+2=11(x+3)+10 | | 7/18+2/9 | | ((v+6)/(v+4))+((v-3)/(v-5))+1 | | 11-b(12)-5= | | x/18+5x/7-3/14 | | 12=21-3m | | 92/5+62/5 | | ((v+6)/(v+4))+((v-4)/(v-5))+1 | | -12+6x=6+5(x-2) | | -4.9=d-2.2 | | 5/+11=18 | | s^2-16s+80=s^2 | | 10+6x-3=2x+7+4x | | -162-7x=2x+63 | | 9=13-s | | 11-(12-5)= | | 3x-2(6x-10)=-6+3(5x+4) | | 5*+11=18 | | -6x-7-5x=-73 | | s^2-16s+80=0 | | 2x(3x+1)-6x^2=4 |

Equations solver categories